Gut microbiota is associated with spatial memory and seed-hoarding behavior of South China field mice (Apodemus draco) - Feng, Enping; Yang, Xifu; Zhao, Kunming; Li, Ying; Zhu, Hanyi; Wang, Zhenshan; Zhang, Zhibin (Frontiers in Microbiology, 2023)
Scatter-hoarding animals store food in multiple locations within their home range and rely on spatial memory for subsequent localization and retrieval. The relationship between memory and scatter-hoarding behavior has been widely demonstrated, but the association of gut microbiota with spatial memory and seed-hoarding behavior of animals remains unclear. In this study, by using enclosure behavior tests, memory tests including an object location test (OLT) and a novel object recognition test (NORT), and fecal microbiota transplantation (FMT) experiment, we evaluated the role of gut microbiota in affecting the memory and seed-hoarding behavior of rodents. According to their scatter-hoarding intensity, South China field mice (Apodemus draco) were divided into scatter-hoarding group (SG) and non-scatter-hoarding group (NG). We found that the SG performed better than the NG in the NORT. FMT from SG donor mice altered the NG recipient mice's gut microbiota structure. Further tests demonstrated FMT from SG donor mice increased memory of NG recipient mice in laboratory tests and seed larder hoarding intensity of NG recipient mice in enclosures. Our results suggest gut microbiota could modulate the memory and seed-hoarding behavior of animals.